Prosze o zrobienie tego zadania ;)

1. Zapisz w prostszej postaci:
a) 7x2(do potegi 2) − 4x − 6x(do potegi 2) + 4 − x(do potegi 2) + 5x = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
b) −2(3a − 2b) − 4a(2 − 3a + 2b) = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
c) (4 − x)(2x + 5) − 4 = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
d) (4 − 2x)(3x − 3) − 2x(3x + 1) = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T17:58:10+01:00
A)...=x+4
b)...=-6a+4b-8a+12a-8b=2a-4b
c)...=8x+20-2x2+5x-4=-2x2+13x+16
d)...=12x-12-6x2-6x-6x2+2x= -12x2+8x-12
2010-02-25T18:01:24+01:00

b) −2(3a − 2b) − 4a(2 − 3a + 2b) = -6a + 4b - 8a + 12a(do potegi 2) - 8ab =-14a + 12a(do potegi 2) - 8ab
c) (4 − x)(2x + 5) − 4 = 8x + 20 - 2x(do potegi 2) - 5x =3x + 20 - 2x( do potegi 2)
d) (4 − 2x)(3x − 3) − 2x(3x + 1) = 12x - 12 - 6x + 6x - 6x(do potegi 2) - 2x=12x - 12 - 6x(do potegi 2)